If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2q = 6 Solving 10 + -2q = 6 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -2q = 6 + -10 Combine like terms: 10 + -10 = 0 0 + -2q = 6 + -10 -2q = 6 + -10 Combine like terms: 6 + -10 = -4 -2q = -4 Divide each side by '-2'. q = 2 Simplifying q = 2
| (-1x-2)-6.5=2.5x+19 | | 3u-4=14 | | 15a^2+1=2 | | -(1-2)-6.5=2.5x+19 | | 4.8q-5.9-5.7q=-19q-4.2 | | 6x(4x-7)(x+5)=0 | | ax-b=y | | 3x+4=5(6-2x) | | .6a=12 | | 62x^2+15x-35= | | 3x^2+12x+48= | | 2v+4=16 | | 4t+3=11 | | 2x-8x+35=5-3x | | 5x-2-2=4x+5 | | 0.0013x^3-0.0667x^2-180=0 | | 3x^2+12x+53= | | 61-81v^2=0 | | 61-81v^2=0 | | 3y+40=70 | | x^2-.2x-8.4=0 | | 3w+3=9 | | 3 w+ 3= 9 | | 81u^2+36u+4=0 | | 2v+6=-4(v+3) | | x^3-3x^2-600=0 | | 4a-(2a+4)= | | v^2+14vy+49y^2=0 | | 4(6x+10)=-8(-4x+7) | | -3(x-5)=x-13 | | -(1x-2)-6.5=2.5x+19 | | 6x+17=15x-111 |